Building next-generation converged networks : theory and practice - Pathan, Al-Sakib Khan (CRC Press, 2013)
The telecommunications industry has seen a rapid boost within the last decade. New realities and visions of functionalities in various telecommunications networks have brought forward the concept of NGN (Next Generation Network). The competitions among the operators for supporting various services, lowering of the cost of having mobile and cellular phones and smart-phones, increasing demand for general mobility, explosion of digital traffic, and advent of convergence network technologies added more dynamism in the idea of NGN. In fact, facilitating convergence of networks and convergence of various types of services is a significant objective of NGN.